Pemanfaatan Limbah Pertanian sebagai Suplemen Nutrisi pada Budidaya Hidroponik Selada Romaine (Lactuca sativa L. var. longifolia) - Saputra, Robby Bagus Saputra; Istirochah Pujiwati; Anis Rosyidah; Dita Agisimanto (Folium : Jurnal Ilmu Pertanian, 2024)
Romaine lettuce is a popular vegetable consumed because of its sweet taste, crunchy texture, and better nutritional content than other types of lettuce. These advantages make its demand continue to increase. Hydroponic is known for its greater harvest potential than conventional systems. However, with the potential for abundant yields, of course, the resulting harvest residue is also increasingly abundant. This waste can be used as organic fertilizer and returned as nutrients to plants. The purpose of this study was to determine the effect of utilizing agricultural waste as a nutritional supplement on hydroponic romaine lettuce cultivation. The study was arranged in a simple RAK with 5 levels of concentration treatment, P0 = 0%; P1 = 20%; P2 = 40%; P3 = 60%; P4 = 80%. The results showed that P0 (control) and P3 (60% concentration) showed results that were not significantly different in plant height, canopy width, and fresh weight. In total fresh weight, P3 (60% concentration) showed the best treatment. Meanwhile, in terms of stomata width, P1 (20% concentration) and P3 (60% concentration) showed no significant differences. However, organic fertilizers have a phytotoxic effect on plants. Based on the correlation test, plant height, canopy width, stomata width, and humidity were positively correlated with total fresh weight.